Effects of recombinant human erythropoietin injections on physical self in endurance athletes - Ninot, G.; Connes, P.; Caillaud, C. (Journal of Sports Sciences, 2006)
This study examined the time course of mean self-esteem and physical self scores in three groups: male endurance athletes treated with recombinant human erythropoietin (rHuEPO group, n = 6), a placebo group (n = 5) injected with a sodium chloride solution and a control group who did not receive any injection (n = 6). Each participant completed the Physical Self Inventory twice a day (between 07.00 and 09.00 h and between 19.00 and 21.00 h). Using a 10 cm visual analog scale, the participants assessed global self-esteem, physical self-worth and the sub-domains of physical condition, sport competence, attractive body and physical strength (Fox & Corbin, 1989). This was conducted over three consecutive periods: in the 2 weeks before the course of injections, during the 6 weeks of injections and for 4 weeks after the injections. Aerobic capacity was assessed before and after 4 weeks of treatment. The results showed a significant increase in aerobic physical fitness in the rHuEPO group and a significant increase in perceived physical condition and physical strength scores at the end of treatment. The main psychological result was that endurance athletes were highly sensitive to the effects of rHuEPO on physical fitness. The perception of increased physical condition may lead to a stronger commitment to training. The rHuEPO injections presented a dangerous hedonic effect linked to endurance training. These results confirm the need to tackle rHuEPO abuse at any time during the training season.